DOZ047.25: Do growth and nutrition influence quality of life in adolescents with esophageal atresia?. (24th June 2019) - Birketvedt, K; Mikkelsen, A; Møinichen, U I; Henriksen, C; Diseth, T H; Boye, B; Malt, U; Mørkrid, L; Jsselstijn, H I; Emblem, R
Abstract: Aim: Adolescents with esophageal atresia (EA) may experience reduced quality of life (QOL) and impaired physical or general health. The aim of this study was to assess health-related QOL in adolescents in relation to physical development. Methods: One hundred and twenty-four EA patients born 1996–2002 and their mothers were identified and enrolled. Twenty-six patients died, 6 excluded; thus 102 were invited. Clinical data were retrieved from medical records. Present physical development was assessed according to national growth references, by height for age (SDS-HFA) and body mass index (SDS-BMI). Energy intake (kcal/kg) was estimated by analysis of 4-day dietary records. Any anamnestic symptoms of gastroesophageal reflux (GER) were registered. EAT-10 questionnaire (modified) was used to assess swallowing difficulties. Participation in any organized spare time activities was registered. Health-related QOL assessment was performed by the age-specific PedsQL 4.0 generic cores scales including proxy-reports. Correlation is reported by Spearman' R. Main Results: Among the 102 patients, 13 older than 18 years were excluded and 34 refused. 55/102 (54%) adolescents with their mothers were included after informed consent (59% boys). Median SDS-HFA was −0.53 (−4.56–1.77), median SDS-BMI 0.16 (−3.91–3.10). Median energy intake was low, 32 kcal/kg (20–69 kcal/kg), compared to the normal range for this age group (43–59 kcal/kg). Only 31/55 (56%) participated in organized activities compared to 80% in a corresponding healthy group. The PedsQL total score and sub score physical health (both for adolescent and for proxy) correlated significantly to GER symptoms ( r = -0.461, P < 0.001) and dysphagia assessed by EAT-10 ( r = −0.329, P = 0.015). The PedsQL total score did not correlate with SDS-HFA, SDS-BMI, energy intake, or participation in organized activities. Conclusion: The presence of dysphagia and GER symptoms seem to influence health-related QOL, with a negative impact on the physical domain. Physical development and energy intake were not related to quality of life.